Modelling the behavioural intentions of day spa customers. Issue 8 (12th March 2020) - Clemes, Michael Daniel; Dean, David L.; Thitiya, Thongkern
Abstract : Purpose: This research develops and tests a comprehensive hierarchical model of the behavioural intentions of day spa customers. Design/methodology/approach: The primary data was collected from the customers of 17 day spas throughout Thailand. EFA and SEM were used to analyse the data and test the interrelationships among service quality, customer satisfaction, perceived value, perceived switching costs and behavioural intentions. A third-order conceptualisation of service quality is also included in the modelling framework. Findings: Customer satisfaction is the key determinant of behavioural intentions. Service quality and perceived value are two important descriptors of customer satisfaction. Service quality is the most important determinant of customer satisfaction, and customer satisfaction is the most significant antecedent of behavioural intentions. Service quality is a significant determinant of perceived value and perceived switching costs. Customer satisfaction plays a partial mediating role on the relationship between service quality and behavioural intentions and between perceived value and behavioural intentions. Originality/value: There is a conceptual gap in the literature as no published empirical research on the day spa industry has comprehensively modelled the behavioural intentions of day spa customers. The comprehensive hierarchical modelling approach used in this study provides a complete and integrative analysis of the constructs under investigation in a day spa context and closes the research gap.